Hazeus ingressus sp. nov. a new goby species (Perciformes: Gobiidae) and a new invasion in the Mediterranean Sea - ENGIN, SEMIH; LARSON, HELEN; IRMAK, ERHAN (Mediterranean Marine Science, 2018)
A new species of gobiid, Hazeus ingressus sp. nov. (Teleostei: Gobiidae) is described from the Levantine coast of Turkey. The species probably originates from the Red Sea and represents the 11th alien gobiid species in the Mediterranean Sea. The new species is distinguished from its Indo-Pacific congeners by a combination of the following characters: no dark blotch on the first dorsal fin; caudal fin coloration; scales in lateral series 25-28 (modally 27); second dorsal fin rays I,8; anal fin rays I,8-9; predorsal scales ctenoid 7; short, stout gill rakers 2+8. This finding suggests that the Lessepsian invasion intensely continues with the inclusion of the known species as well as undescribed species.